Proctological Diseases in Surgical Practice - Cianci, Pasquale (IntechOpen, 2018)
The prevalence of anorectal disorders in the general population is probably much higher than that seen in clinical practice. Anorectal diseases have for a long time been considered of little interest, with their treatment considered of little prestige despite the social impact they cause to patients. Proctology was initiated late and developed slowly over the years. However, in the last 20 years, a renewed interest has begun, and today, we can say that proctology is a specialized branch of general surgery. This book "Proctological Diseases in Surgical Practice" provides a practical introduction to proctology, with a particular attention to the topics that have not yet been investigated. This book may be useful for the general physician as well as for the specialist.